Implementasi Kebijakan Pemberian ASI Eksklusif Di Palembang Dalam Mendukung Hak Ibu Menyusui - Anggraini, Dewi Ratih; Satispi, Evi; Sulastri, Endang; Andriyansyah, Andriyansyah; Suradika, Agus; Setiadin, Setiadin (SOCIETAS, 2024)
This research discusses the alignment of breastfeeding mothers by the Palembang City Government through the issuance of Palembang City Regulation No. 2 of 2014 concerning Exclusive Breastfeeding, where this policy has generally been able to increase awareness and concern for breastfeeding mothers to continue to be able to provide exclusive breastfeeding to their babies, especially in the 0-6 month period after their birth. The policy issued by the Palembang City Government generally regulates various things in an effort to create a comfortable and safe atmosphere for a breastfeeding mother, especially in providing guarantees for the alignment of all parties including family, environment, and government to breastfeeding mothers to continue to be able to carry out exclusive breastfeeding activities for their babies. The research used a qualitative method with a library research design or literature review. The data used is the result of a review of studies that have been conducted by previous researchers in accordance with the theme of the Implementation of Exclusive Breastfeeding Policies in Supporting the Rights of Breastfeeding Mothers.